2006
DOI: 10.1002/art.21696
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of utilization patterns and cost implications of coxibs among seniors in Quebec, Canada: What is the potential impact of the withdrawal of rofecoxib?

Abstract: Conclusion. Celecoxib appears to be a more expensive therapeutic option than rofecoxib due to a relatively higher daily dose and tablet consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The choice of algorithms was made according to the most prevalent chronic pain syndromes in the QPR (Table ). Although previous administrative database studies reported algorithms for postherpetic neuralgia, osteoarthritis, migraine, headaches, rheumatoid arthritis, irritable bowel syndrome, and systemic lupus erythematous, the prevalence of such conditions was ≤2.5% in our sample (Table ) and did not allow us to estimate validity statistics. The validity of single pain codes (307.8, 338, 338.2, or 338.4) was also investigated (end of Table ).…”
Section: Methodsmentioning
confidence: 69%
“…The choice of algorithms was made according to the most prevalent chronic pain syndromes in the QPR (Table ). Although previous administrative database studies reported algorithms for postherpetic neuralgia, osteoarthritis, migraine, headaches, rheumatoid arthritis, irritable bowel syndrome, and systemic lupus erythematous, the prevalence of such conditions was ≤2.5% in our sample (Table ) and did not allow us to estimate validity statistics. The validity of single pain codes (307.8, 338, 338.2, or 338.4) was also investigated (end of Table ).…”
Section: Methodsmentioning
confidence: 69%